Non c’è libertà senza identità. Intervista di Paolo Izzo a Massimo Fagioli - Izzo, Paolo; Fagioli, Massimo (Il sogno della farfalla, 2024)
In this interview, published for the first time in 2007, Fagioli offers an analysis of historical movements, in particular of the left, between the 1960s and 1970s. Addressing the themes of freedom, identity and desire in the light of Human Birth Theory, the psychiatrist traces a reconstruction of great originality and relevance.